The Influence of Workload, Work Stress and Work-Life Balance on Turnover Intention in Generation Z Employees in Yogyakarta Special Region - Maharani, Natasya; Santosa, Awan (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the influence of workload, work stress and work-life balance on turnover intention in generation z employees in the special area of Yogyakarta. The sample consists of 100 employees with primary data collected through Google Form questionnaires. Data analysis was carried out with a Likert scale and statistical tests using SPSS. The results showed a positive and significant effect of Workload and Job Stress on Turnover Intention, while Work-life Balance had no significant effect. The implication of this result can help the Company in reducing employee Turnover Intention.